Guideline for the Conduct of Clinico-Pathological Conference (CPC) - Nasuruddin, Muhammad Haidar; Che Ahmad, Aminudin; Ab Rahman, Jamalludin (DRRARA RESOURCES, 2021)
A guideline for clinico-pathological conference conduct and presentation which is implemented in authors' centre.